Perancangan Mesin Peniris Minyak Bawang Goreng Otomatis - Marojahan Hutasoit, Alex; Hermanto, Tino; Fahrul Sinurat, Ryan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2024)
Shallots are one of the horticultural commodities with great potential and should be developed into high-quality products. One of the processed products from shallots is fried shallots, which are used to enhance the flavor of food. Fried shallots are a sought-after culinary product, particularly among homemakers, snack bar owners, and others. The aim of this research is to design an automatic fried shallot oil draining machine for home industry scale. This research method utilizes AutoCAD software for design planning. The results of this design show that the required electric motor power is 0.85 Hp, the motor pulley and drive shaft pulley ratio is 1:2, with the motor pulley being 60 mm and the drive shaft pulley 120 mm, the shaft diameter is 30 mm, and the oil draining drum diameter is 580 mm with a height of 590 mm, using stainless steel material. The design yields a draining machine capable of continuous operation with the planned production capacity.